Study of genetic variability and analysis of possible kdr mutations in the gene encoding sodium channels related to resistance of Aedes aegypti to insecticides - Chiele , Andreina Heineck; Florentino, Iara Natália Afonso; Schulz , Rafael Giordani; Figueiredo, Elisson Furlan; Librelotto, Carina Sperotto; Colacite, Jean (Research, Society and Development, 2023)
Introduction: Mosquitoes of the genus Aedes, especially Aedes aegypti, have a higher prevalence in tropical countries and because they are located in urban environments, they are currently considered the main vectors of arboviruses such as Dengue, Zika, Chikungunya, Yellow Fever, among others. Dengue is one of the most widespread and worrying diseases for public health, as it is characteristic of a seasonal epidemic, and because many insecticides used in smokeless cars are no longer effective against the vector, which makes its control difficult, this study aimed to analyze the genetic profile of Aedes aegypti larvae based on the detection of the mtDNA NADH4 gene, and to analyze possible kdr mutations in the gene that encodes sodium channels related to resistance to insecticides. Materials and method: The kdr mutation research was analyzed based on in the restriction fragment length polymorphism technique (PCR-RFLP) Results: Of the 52 samples analyzed, 24 presented showed polymorphism of bands in the agarose run, confirming the mutation Conclusion: The results obtained in the present study indicated the presence of almost 50% of larvae with mutation for resistance.